Inside Cover: Hybridization of a Flexible Cyclooctatetraene Core and Rigid Aceneimide Wings for Multiluminescent Flapping π Systems (Chem. Eur. J. 8/2014). Issue 8 (17th February 2014) - Yuan, Chunxue; Saito, Shohei; Camacho, Cristopher; Kowalczyk, Tim; Irle, Stephan; Yamaguchi, Shigehiro
<x xml:space="preserve">Abstract</x> Hybridization of flexible and rigid π‐conjugated frameworks produces a series of multifluorescent flapping π systems. A flexible cyclooctatetraene core and rigid aceneimide wings with various π‐conjugation lengths have been designed and synthesized. While these molecules have a V‐shaped bent conformation in the ground (S0) state, the bent structure is changed to a planar conformation in the lowest excited singlet (S1) state irrespective of the lengths of the aceneimide wings. For more details, see the Full Paper by S. Saito, S. Irle, S. Yamaguchi et al. on page 2193 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>